Levantamento e análise dos métodos de integração BIM-ACV para tomada de decisão no processo de projeto - Queiroga, Thaina Barbosa (2023)
The Architecture, Engineering and Construction (AEC) sector has been identified as one of the main agents of environmental impacts. Within this context, it is necessary to adopt new strategies that make the sector more sustainable. Therefore, the integration between the Life Cycle Assessment (LCA) and Building Information Modeling (BIM) methodologies has shown to be promising in supporting decision-making in the development of projects with lower environmental impact. Thus, the present research aims to carry out a survey of the different integration methods, evaluating their application potentialities and limitations and proposing general application guidelines throughout the design process. For this, a Systematic Review of Literature was carried out in order to develop a critical analysis of what has already been studied. In this critical analysis, it was possible to perceive that the methods developed by the analyzed authors, most of them dealt with practical methods for BIM-ACV integration, using case studies to evaluate what was developed. Several databases were used as a source of information, as well as the adoption of more than one for the development of a method. With these studies found of the approaches that contemplate a matrix such as the evaluation potentialities and methods based on the BIM-ACV integration proposals in the most recurrent and depending on the project. Thus, for the initial stages of the project, with the objective of only guiding the first decision decisions, an approach is suggested that uses plug-ins to perform a quick analysis. Already in the stages, they must be used in the design, it is to obtain more results and, therefore, more assertive in favor of the improvements of the methods calculated with precision. Thus, the use of visual programming routines with ACV export with 3D model promissory strategies are. For, in the last final stages of the project, due to the moment to seek the results closer to reality, they can still be used for the presentation of certifications and environmental seals. Thus, in this way, the same strategy of the phase itself is maintained or it can be even within the model's plug-ins configuration. All the strategies of the proposals present their potential and solutions, and their applications are viable in all types of projects. Therefore, it is suggested for future works to carry out long case studies of the design process, as the approaches evaluated here, in order to assess that they safely approach the results.